Kinetics of Hepatitis B Virus Infection: A Cellular Automaton Model Study - Gharib-Zahedi1, Mohammad Reza; Ghaemi, Mehrdad (Archives of Advances in Biosciences, 2012)
We created a simple cellular automata (CA) model for hepatitis B infection dynamics associated with spatial structure performed under various ages of liver tissue correspond to different immune responses in order to study the effect of spatial heterogeneities on the dynamical evolution of a viral infection. The results of the simulations show biphasic nature of viral load decreases, as observed in the acute infection in real state. Our results also confirm the importance of the hepatocyte target cells, the spatial localization, and the local interactions on the dynamics of HBV infection, whereas models based on ordinary differential equations are not considered. Our model is quite simple with four states and only five parameters, however, the dynamics from the model qualitatively equivalent clinical data.